2022
DOI: 10.1097/spv.0000000000001221
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Infiltration of Local Anesthetics During Vaginal Hysterectomy: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Importance Vaginal hysterectomy (VH) is the preferred route of choice for women desiring hysterectomy to treat uterine pathology, including premalignant conditions and fibroids. Objective The aim of this study was to evaluate the impact of the use of preemptive local analgesia (LA) on postoperative pain and perioperative outcomes for women undergoing VH. Study Design A systematic search of 4 electronic datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Administering preemptive locoregional analgesia attenuates postoperative pain [ 14 16 ], decreases supplemental analgesic requirement, and prolongs the average time to the first use of rescue analgesic drugs in various procedures. Moreover, Lee et al showed that the pre-incisional thoracic paravertebral block conferred a significant preemptive visceral analgesic effect and significantly reduced the amount of postoperative opioid consumption [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Administering preemptive locoregional analgesia attenuates postoperative pain [ 14 16 ], decreases supplemental analgesic requirement, and prolongs the average time to the first use of rescue analgesic drugs in various procedures. Moreover, Lee et al showed that the pre-incisional thoracic paravertebral block conferred a significant preemptive visceral analgesic effect and significantly reduced the amount of postoperative opioid consumption [ 16 ].…”
Section: Discussionmentioning
confidence: 99%